PERTANGGUNGJAWABAN PELAKU USAHA KEPADA KONSUMEN TERHADAP PROMOSI YANG TIDAK BENAR DITINJAU DARI UNDANG-UNDANG NOMOR 8 TAHUN 1999 TENTANG PERLINDUNGAN KOSUMEN (STUDI KASUS DI TOKO ALFAMART KECAMATAN SAIL) - Yemima Br. Sitepu; Maryati Bachtiar; Riska Fitriani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
Consumer protection against the campaign conducted in the District Sail Shop Alfamart need for supervision, it is caused because so many business do promotion on a particular item. But often once the promotion is done in a manner that is false or misleading consumers, so the promotion is done by business often result in a loss for consumers. A result of the improper promotion, businesses should be held responsible for damages suffered by consumers. Alfamart District Shop of Sail is found that many of these promotions were misleading the public, so that many consumers feel very aggrieved. So based on this it is necessary that both consumer protection and the supervision of the government campaign against improper conducted in the District Sail Alfamart store.Keywords: Accountability - Business Actors - Promotion Not True